Isolation of SAT2 Foot and Mouth Disease Virus in Iraq - K AL-Anbagi, Ghazwan; B Allawe, Aida (The Iraqi Journal of Veterinary Medicine, 2025)
Foot-and-mouth disease (FMD) is a highly contagious viral disease affecting cloven-hoofed animals, causing significant economic losses in livestock industries. The causative agent, Foot-and-Mouth Disease Virus (FMDV), consists of seven serotypes: O, A, C, South African Territories (SAT) 1, SAT2, SAT3, and Asia1. These serotypes are lack of cross-protection even among variants of the same serotype. This study aimed to isolate and identify the SAT2 serotype from Iraqi cattle, using molecular techniques and cell culture methods. A total of 100 samples, including the tongue epithelial tissue and vesicular fluid, were collected from suspected FMD cases in Diyala, Baghdad, Kirkuk, Babylon, and Salahaddin provinces between July 2023 and October 2024. The RNA was extracted, and real-time quantitative polymerase chain reaction (RT-qPCR) was conducted. Primers targeting the 3D gene were used to detect FMDV, while specific primers targeting the 1D gene were employed for the SAT2 serotype identification. The virus isolation was performed on secondary sheep testis (SST) cell cultures, and then the cytopathic effects (CPE) were reported with calculating the tissue culture infectious dose 50% (TCID50) was calculated using the Reed and Muench method. The FMDV was detected in 85 samples (85%), among which 30 (35.3%) were positive for the SAT2 serotype. The virus isolation from five representative samples revealed characteristic CPE, including cell rounding, degeneration, and syncytia formation. The RT-qPCR confirmed presence of the SAT2 serotype. The TCID50 ranged from Log106.8 TCID50/mL to Log107.05 TCID50/mL. The present study successfully isolated the SAT2 serotype of the FMDV in Iraq for the first time. It underscores the importance of molecular diagnostics and virus isolation in surveillance and highlights the need for targeted vaccination strategies against SAT2‎‎‎.